Restriction assay for integrative recombination of bacteriophage lambda DNA in vitro: requirement for closed circular DNA substrate. - Mizuuchi, K (1976)
A novel assay has been developed for in vitro genetic recombination of DNA. Substrate and product DNAs are cleaved with a restriction endonuclease and the resulting fragments are separated by electrophoresis in agarose gels. The substrate DNA has been chosen so that the recombination to be studied deletes a segment of DNA. The remaining DNA gives rise to a unique restriciton fragment, as does the DNA segment that has been removed. The method provides a convenient and physical, rather than genetic, assessment of the conversion of parental to recombinant DNA. This method has been applied to an in vitro system that carries out integrative recombination of bacteriophage lambda. We find that, different molecular forms of DNA tested, closed circular DNA is the only efficient substrate. Linear DNA and three kinds of circular DNA containing interruptions are at best very poor substrates. The implications of this surprising result are discussed. In addition, we show that the in vitro recombination system completes the breaking and rejoining steps of recombination. No stable DNA intermediates involving chiasmata or broken end structures are found.